The microclimate benefits of street and park trees in Putrajaya - Zainurdin, Effa Mulia (2018)
Urbanization alters the urban environment and climate. Green infrastructure such as trees in the urban area plays an important role in mitigating the microclimate. Therefore, this study investigated the benefits of street and park trees in Putrajaya. The main objectives of this study were to compare the microclimatic condition between residential street and urban park at Taman Saujana Hijau. In addition, this study also aimed to evaluate association between the distance from urban park and microclimate benefits. Microclimate variables such as air temperature, relative humidity, wind speed, and solar radiation were measured at both sites. Results from this study showed that that trees in the park had greater micro climate benefits compared to the residential area where mean of air temperature at park was 34.3°C while in the street was 35.5°C. Distance from urban park influenced the microclimate as the air temperature and solar radiation were increased with distance especially during solar noon due to canopy openness. These results showed that trees urban park provides better microclimate benefits than trees in the street due to greater canopy coverage in the park. This study will be beneficial to the urban forest managers to increase tree coverage in the street areas to improve the street microclimate.